2022
DOI: 10.7759/cureus.23721
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Prolactin With Type 2 Diabetes Mellitus: A Comparative Cross-Sectional Study From South India

Abstract: Background: The association of serum prolactin (PRL) with diabetes is still uncertain, with a paucity of data in the south Indian population. This study aims to compare the serum PRL levels between type 2 diabetes mellitus (T2DM) patients and normoglycaemic volunteers and correlate the serum PRL level with fasting plasma glucose (FPG), postprandial plasma glucose (PPG), glycated haemoglobin (HbA1c) levels, and the lipid profile in the study population. Methods: This was a comparative cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(28 reference statements)
1
1
0
Order By: Relevance
“…BV=Bee venom, SEM=Standard error of the mean FSH, and LH levels and an elevated level of prolactin [40,41]. However, some studies showed a reduced level of testosterone and prolactin [42,43] and an increased level of LH with no change in the FSH level [43]. The latter results are in line with this study's results.…”
Section: Discussionsupporting
confidence: 91%
“…BV=Bee venom, SEM=Standard error of the mean FSH, and LH levels and an elevated level of prolactin [40,41]. However, some studies showed a reduced level of testosterone and prolactin [42,43] and an increased level of LH with no change in the FSH level [43]. The latter results are in line with this study's results.…”
Section: Discussionsupporting
confidence: 91%
“…In the normoprolactinemic population in general, higher PRL levels within the normal range were associated with improved insulin sensitivity and glucose metabolism, and lower prevalence of diabetes and metabolic syndrome ( 85 88 ). Nevertheless, some studies showed that PRL levels were inversely associated with T2D risk ( 89 , 90 ), particularly in women ( 91 , 92 ), while others show a positive or no association in clinical cohorts including men and women ( 93 , 94 ). A recent meta-analysis ( 95 ) reported that a higher PRL level within the normal range was associated with reduced risk of prevalence but not incidence T2D.…”
Section: Insulin Resistance and Hyperglycemiamentioning
confidence: 99%